Short-Term Ecogeomorphic Evolution of a Fluvial Delta from Hindcasting Intertidal Marsh-Top Elevations (HIME) - Brittany C. Smith; Kevan B. Moffett; David Mohrig (Remote Sensing, 2020)
Understanding how delta islands grow and change at contemporary, interannual timescales remains a key scientific goal and societal need, but the high-resolution, high frequency morphodynamic data that would be most useful for this are as yet logistically prohibitive. The recorded water levels needed for relative elevation analysis are also often lacking. This paper presents a new approach for hindcasting intertidal marsh-top elevations (HIME) to resolve ecogeomorphic change, even in a young, rapidly changing fluvial delta setting, at sub-decadal temporal resolution and at the spatial resolution of widely available optical remote sensing imagery (e.g., 30 m Landsat). The HIME method first calculates: (i) the probability of land exposure in a set of historical imagery from a user-defined discrete timespan (e.g., months or years); (ii) the probability of water level non-exceedance from water level records, which need not be complete nor coincident with the imagery; and (iii) the systematic variation in local mean water level with distance along the primary hydraulic gradient. The HIME method then combines these inputs to estimate a marsh-top elevation map for each historical timespan of interest. The method was developed, validated, applied, and results analyzed to investigate time-lapse evolution of the Wax Lake Delta in Louisiana, USA, every three years, over two decades (1993–2013). The hindcast maps of delta island extents and elevations evidenced ecogeomorphic system self-organization around four stable attractors, or elevation platforms, at about −0.3 m (subtidal), 0.2 m, 0.4 m, and 0.9 m (supratidal) NAVD88. The HIME results also yielded a time series of net subaerial sediment accumulation, and specific locations and magnitudes of gains and losses, at scales from 30 m to delta-wide (~100 km3) and 6 to 21 years. Average subaerial net sediment accumulation at the Wax Lake Delta (WLD) was estimated as 0.6 cm/yr during the study period. Finally, multiple linear regression models were successfully trained on the HIME elevation maps to model evolving delta island morphologies based on simple geometric factors, such as distance down-delta and position on a delta island; the models also successfully reproduced an average delta topset slope of 1.4 cm. Overall, this study’s development and application of the HIME method added detailed insights to recent, transient ecogeomorphological change at the WLD, and demonstrated the potential of the new approach for accurately reconstructing past intertidal topographies and dynamic change.